2021
DOI: 10.1186/s10194-021-01361-0
|View full text |Cite
|
Sign up to set email alerts
|

Which is the best transcranial direct current stimulation protocol for migraine prevention? A systematic review and critical appraisal of randomized controlled trials

Abstract: Background Transcranial direct current stimulation (tDCS) could counteract the pathophysiological triggers of migraine attacks by modulating cortical excitability. Several pilot randomized controlled trials (RCTs) assessed the efficacy of tDCS for migraine prevention. We reviewed and summarized the state of the art of tDCS protocols for migraine prevention, discussing study results according to the stimulations parameters and patients’ populations. Main body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 56 publications
(112 reference statements)
1
9
0
Order By: Relevance
“…DLPFC directly promotes or inhibits pain through coordination with these brain regions or through modulating the activity of pain descending inhibition pathways ( 31 ). Therefore, DLPFC-rTMS was able to reduce pain sensation, as supported by several recent studies, like spinal cord injury ( 12 ), migraine ( 13 ) and fibromyalgia ( 14 ). In this study, we hypothesized that DLPFC-rTMS may also be effective in the treatment of cancer pain and thus conducted this trial.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…DLPFC directly promotes or inhibits pain through coordination with these brain regions or through modulating the activity of pain descending inhibition pathways ( 31 ). Therefore, DLPFC-rTMS was able to reduce pain sensation, as supported by several recent studies, like spinal cord injury ( 12 ), migraine ( 13 ) and fibromyalgia ( 14 ). In this study, we hypothesized that DLPFC-rTMS may also be effective in the treatment of cancer pain and thus conducted this trial.…”
Section: Discussionsupporting
confidence: 59%
“…Usually, low frequency (< 1Hz) stimulation has an inhibitory effect on the brain, while high frequency (> 5Hz) stimulation excite neurons ( 11 ). It has been reported that rTMS relieves various types of pain, such as neuropathic pain after spinal cord injury, stroke or postoperative of trigeminal nerve ( 12 ), migraine ( 13 ), fibromyalgia ( 14 ) and chronic musculoskeletal pain ( 15 ). Even less clinical study has been done on the application of rTMS in patients with cancer pain.…”
Section: Introductionmentioning
confidence: 99%
“…So far, several studies have already evaluated tDCS for migraine prevention proving that it is a promising treatment to prevent migraine ( 36 , 40 50 ). Available RCTs included a variable number of patients (from 15 to 135 patients) with highly heterogeneous patient populations, outcomes, time schedules, and tDCS montages ( 34 ). Most of the available RCTs performed either cathodal occipital stimulation with anterior reference ( 40 , 43 , 44 , 46 ) or anodal frontal stimulation with supraorbital reference ( 36 , 41 , 42 , 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…Results of those RCTs were overall positive in the short term, while being more controversial 12 months after tDCS ( 36 , 48 ). The available RCTs are limited by the underuse of neurophysiological tests, which would improve our understanding of the effect of tDCS and how to improve it ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation